The ultrasonically treated nanoliposomes containing PCV2 DNA vaccine expressing gC1qR binding site mutant Cap is efficient in mice - Du, Qian; Shi, Tengfei; Wang, Huaxin; Zhu, Changlei; Yang, Nan; Tong, Dewen; Huang, Yong (Frontiers in Microbiology, 2023)
Nowadays, vaccines are broadly used to prevent porcine circovirus type 2 (PCV2) infection-induced expenditures, but the virus is still spreading among pigs. The current PCV2 vaccines all rely on the immunogenicity of Cap, yet our previous studies found that Cap is also the major component mediating the PCV2 infection-induced immune suppression through its interaction with host gC1qR. Thereby, new vaccines are still necessary for PCV2 prevention and control. In this study, we constructed a new PCV2 DNA vaccine expressing the gC1qR binding site mutant Cap. We introduced the Intron A and WPRE elements into the vector to improve the Cap expression level, and fused the IL-2 secretory signal peptides to the N-terminal of Cap to mediate the secretion of Cap. We also screened and selected chemokines CXCL12, CCL22, and CCL25 to migrate dendritic cells. In addition, we contained the vectors with PEI and then ultrasonic them into nano size to enhance the entrance of the vectors. Finally, the animal experiments showed that the new PCV2 DNA vaccine expressing the gC1qR binding site mutant Cap could induce stronger humoral and cellular immune responses than the PCV2 DNA vaccine expressing the wild-type Cap and the non-ultrasonic treated PCV2 DNA vaccine in mice, and protect the mice from PCV2 infection and lung lesions. The results indicate the new PCV2 DNA vaccine expressing the gC1qR binding site mutant Cap has a certain development value, and provide new insight into the development of novel PCV2 vaccines.